Stress and quality of sleep in undergraduate nursing students - Kézia Katiane Medeiros da Silva; Milva Maria Figueiredo de Martino; Clarissa Maria Bandeira Bezerra; Ângela Monic Lima de Souza; Danila Maria da Silva; Jacqueline Targino Nunes
ABSTRACT Objective: to analyze the level of stress and sleep quality in nursing students according to terms of the nursing program. Method: descriptive and cross-sectional research developed in a higher education institution in Northeastern Brazil on 167 students. We used data collection, sociodemographic information, and a scale for assessing stress and sleep quality in nursing students. Results: we identified a statistically significant difference between domains of the stress scale and the terms of the undergraduate program, and between the quality of sleep and such terms such as as in the fourth and sixth semesters. Conclusion: different stress scores show that the semester which concerns students the most is the fifth. Quality of sleep was deemed good for the first, third, fifth, seventh, and eighth semesters; and poor for the fourth and sixth terms.